Evaluasi Kebijakan Penyediaan Jalan Usaha Tani dalam Memenuhi Kebutuhan dan Kesejahteraan Petani di Nagari Lansek Kadok Barat - Sahriana Sahriana; Putri Febri Wialdi (Lembaga Yasin AlSys, 2026)
Jalan Usaha Tani (JUT) is an important infrastructure in supporting the smooth operation of agricultural activities and improving farmers’ welfare, but its provision in Nagari Lansek Kadok Barat has not been implemented optimally, thereby causing various problems for the farming community. This study aims to evaluate the policy for the provision of JUT based on Law Number 19 of 2013 and Minister of Agriculture Regulation Number 52 of 2018, to identify the inhibiting factors in its implementation, and to analyze its impact on fulfilling farmers’ needs and welfare. This study used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The research informants included nagari officials, subdistrict authorities, farmer groups, and farmers, while data analysis was conducted using an interactive model consisting of data reduction, data presentation, and conclusion drawing. The results showed that, conceptually, the policy for the provision of JUT had been understood and planned participatively, but its implementation had not been optimal due to budget limitations, the priority use of village funds, the lack of support from the regency government, and dependence on external assistance. These conditions affected difficulties in agricultural activities, increased transportation costs, dependence on middlemen, and declining farmers’ income and welfare. These findings affirm that the effectiveness of the JUT provision policy requires increased budgetary support and strengthened intergovernmental synergy so that agricultural infrastructure development can be implemented more effectively and equitably to support farmers’ welfare.